2016
DOI: 10.1093/humrep/dew019
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death-1 (PD-1) and T-cell immunoglobulin mucin-3 (Tim-3) regulate CD4+T cells to induce Type 2 helper T cell (Th2) bias at the maternal–fetal interface

Abstract: This study was supported by the National Basic Research Program of China (2015CB943300); National Nature Science Foundation of China (81490744, 91542116, 31570920, 81070537, 31171437, 81370770, 31270969, 31570920, 91542116); the Key Project of Shanghai Municipal Education Commission (14ZZ013) and the Key Project of Shanghai Basic Research from Shanghai Municipal Science and Technology Commission (12JC1401600). None of the authors have any conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 32 publications
6
75
1
5
Order By: Relevance
“…More importantly, recent studies have revealed that SGK1 selectively differentiated T H 1 and T H 2 CD4 + T cells 36. Such observations are of great importance to embryo implantation and the subsequent maintenance of pregnancy, as the feto-maternal interface predominantly favors a T H 2 type of intrauterine immunity 37. Therefore, we wondered whether E 2 -activated SGK1 affected the production of pro-inflammatory and T H 1 cytokines in LPS-challenged DSCs as well as the transduction pathways involved.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…More importantly, recent studies have revealed that SGK1 selectively differentiated T H 1 and T H 2 CD4 + T cells 36. Such observations are of great importance to embryo implantation and the subsequent maintenance of pregnancy, as the feto-maternal interface predominantly favors a T H 2 type of intrauterine immunity 37. Therefore, we wondered whether E 2 -activated SGK1 affected the production of pro-inflammatory and T H 1 cytokines in LPS-challenged DSCs as well as the transduction pathways involved.…”
Section: Resultsmentioning
confidence: 96%
“…SGK1 was found to facilitate T H 2 differentiation by phosphorylating Nedd4-2 to inhibit degradation of the transcription factor JunB under the T H 2-polarizing conditions, while suppressing the generation of T H 1 cytokines 36. These findings are of particular importance to the maintenance of gestation, as the feto-maternal interface primarily favors a T H 2 shift 37.…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 years ago, Saito and colleagues observed that in the first trimester of human normal pregnancy, decidual CD4 + T (dCD4 T) cells express the T-cell-activation antigens CD69, HLA-DR, interleukin-2 receptor-alpha (IL-2Rα), and IL-2Rβ at a significantly higher level than do peripheral blood CD4 + T (pCD4 T) cells, indicating that dCD4 T cells are regionally activated at an early stage of pregnancy (17). Furthermore, recent studies showed that dCD4 T cells in early pregnancy express higher levels of the T regulatory (Treg)-cell markers CD25 and FOXP3, the proliferation-associated antigen Ki-67, programmed cell death-1 (PDCD1, also called PD-1), and T-cell immunoglobulin mucin-3 (Tim-3) than their peripheral blood counterparts (13, 1820). However, the complexity of dCD4 T cells has not been well elucidated, and a thorough understanding of the molecular and functional features of these cells would shed light on their eventual roles during early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal Tim-3 level might be associated with RSA (27). As described by Wang et al Tim-3 promotes T-helper balance (28).…”
Section: Introductionmentioning
confidence: 87%